Demokrasi dan Tata Kelola Keuangan Publik Indonesia pada Era Desentralisasi Fiskal - Dina; Eko Ribawati (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2026)
The implementation of fiscal decentralization since 2001 has become a pivotal milestone in transforming Indonesia’s governance system and public financial management. The delegation of fiscal authority to local governments is expected to enhance regional financial independence while strengthening transparency and accountability in budget administration. This study aims to analyze the relationship between democracy and public financial governance in the era of fiscal decentralization, as well as to assess the application of transparency, accountability, and public participation at the regional level. Using a qualitative approach through a literature review method, this research draws on secondary sources including scholarly publications, government documents, and recent academic studies. The findings indicate that fiscal decentralization has the potential to reinforce democratic fiscal practices, although its implementation is still limited by bureaucratic capacity constraints, the influence of local political elites, and weak public oversight mechanisms. Conversely, the adoption of digital technologies in financial governance has enhanced efficiency, transparency, and accountability, despite requiring stronger human resource capacity and consistent political commitment. Keywords: Accountability, Democratic Fiscal Governance, Decentralization, Public Participation